Reseña - Jaramillo Marín, Jefferson (2014)
Rodríguez-Idárraga, Nicolás. Los vehículos de la memoria. Discursos morales durante la primera fase de la violencia (1946-1953). Bogotá: Universidad de los Andes, 2008.